Vertebral Compression Fracture in a Patient with Hyperthyroidism - Ayhan Kul; Buminhan Seferoğlu; Kazım Şenel; Fatih Bağcıer (Galenos Yayinevi, 2016)
Osteoporosis in men is an important public health problem, and its prevalence is increasing as the population ages. Although it is traditionally considered as a women's health issue, osteoporosis-related mortality and morbidity rates are higher in men. Although the lifetime risk of the hip fracture is lower in men than women, men are twice as likely to die after a hip fracture. All men diagnosed with osteoporosis should be evaluated for secondary causes of bone loss, such as hypogonadism, the use of corticosteroid, smoking, excessive alcohol consumption, low calcium intake, vitamin D deficiency and hypothyroidism. Here, we aimed to present a male patient in whom osteoporotic a vertebral fracture was detected and who was diagnosed with hyperthyroidism.